Clinical and Prognostic Significance of Idiopathic Left Bundle-Branch Block in Young Adults - Pietro Delise; Luigi Rivetti; Giuseppe Poletti; Monica Centa; Giuseppe Allocca; Nadir Sitta; Arianna Cati; Giovanni Turiano; Emanuela Lanari; Paolo Zeppilli; Luigi Sciarra (Cardiology Research and Practice)
Aims. LBBB is rare in healthy young adults, and its long-term prognosis is uncertain. Methods. 56 subjects (aged <50 years), in whom an LBBB was discovered by chance in the absence of clinical and echocardiographic evidence of heart disease, were collected in a multicenter registry. Results. 69% were males. Mean age at the time of discovery of LBBB was 37 ± 11 years. Mean QRS duration was 149 ± 17 m sec and 35% had left axis deviation. All patients had a normal echocardiogram, except for left ventricular dyssynchrony; 37 patients underwent coronary angiography (30) or myocardial scintigraphy during effort Eriksson and Wilhelmsen (2005), and in all cases obstructive coronary artery disease was excluded. In 2/30 patients who underwent coronary angiography, an anomalous origin of the CX artery from the right coronary sinus was found. Thirty patients underwent cardiac magnetic resonance; in 60% it was normal, while in 40% it revealed late enhancement, which in 33% was localized in the basal septum, suggesting fibrosis of the left bundle branch. During follow-up (12+/10 years, median 10 years) no sudden death occurred. At the end of follow-up, all patients were alive, except for one who suffered accidental death. Two patients (3.5%) underwent PM implantation owing to syncope. The echocardiogram at the end of follow-up revealed LV dysfunction in only one patient. Conclusions. In young adults without apparent heart disease, LBBB is a heterogeneous condition. In the vast majority of cases, the prognosis is good and no ventricular dysfunction occurs over time. However, as only 18% of our patients were aged >60 years at the end of follow-up, we cannot establish the prognosis in older age-groups.